Percutaneous lipiodol lymphangiogram in chylous leakage successful embolisation post mastectomy: a case report - Mohd Yaakob, Mohd Naim; Abdul Rahim, Ezamin; Md Noh, Mohamad Syafeeq Faeez; Kamis, Mohd Fandi Al Khafiz; Shukri AS, Mohd Hady (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Complication of chyle leakage is rare post mastectomy, ranging from 0.36 – 0.84%. This case report discuses a rare case of chylous leakage post mastectomy in a 79-year-old female. The complication was suspected when the draining colour of axillary drainage change from serous fluid to milky colour, diagnosis then confirmed clinically and biochemically as chyle. The patient was initially managed conservatively, but this was not successful and was referred to an interventional radiology for lymphangiogram and embolization. Percutaneous lipiodol embolization was performed with immediate success.